2015
DOI: 10.1016/j.neuropsychologia.2015.05.032
|View full text |Cite
|
Sign up to set email alerts
|

The right insula contributes to memory awareness in cognitively diverse older adults

Abstract: Unawareness of memory loss is a challenging characteristic of Alzheimer’s disease (AD) and other age-related neurodegenerative conditions at their earliest stages, adversely affecting important outcomes such as patient decision making and safety. The basis of this metacognitive disturbance has been elusive; however it is almost certainly determined in part by compromise to brain regions critical for self-assessment. The subjectivity of traditional measurements of self-awareness in dementia has likely limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 63 publications
6
84
2
1
Order By: Relevance
“…Lower FOK accuracy was associated only with smaller right insular volume in this group of cognitively diverse older adults. Cosentino et al (2015) discussed the role of the insula in memory awareness in the context of its contribution in conscious detection of errors assuming that it could be consistent with a form of primary or secondary executive anosognosia proposed in the CAM model (Hannesdottir and Morris 2007). …”
Section: Brain Substrates Of Metamemorymentioning
confidence: 90%
See 1 more Smart Citation
“…Lower FOK accuracy was associated only with smaller right insular volume in this group of cognitively diverse older adults. Cosentino et al (2015) discussed the role of the insula in memory awareness in the context of its contribution in conscious detection of errors assuming that it could be consistent with a form of primary or secondary executive anosognosia proposed in the CAM model (Hannesdottir and Morris 2007). …”
Section: Brain Substrates Of Metamemorymentioning
confidence: 90%
“…Recently, relations between memory awareness assessed using a modified episodic FOK task and structural integrity of brain regions implicated in self-awareness processes (i.e., prefrontal, temporal, parietal, anterior and posterior cingulate cortices, hippocampus and insula) were investigated in a mixed group of patients with mild Alzheimer’s disease and cognitively healthy older adults (Cosentino et al 2015). Lower FOK accuracy was associated only with smaller right insular volume in this group of cognitively diverse older adults.…”
Section: Brain Substrates Of Metamemorymentioning
confidence: 99%
“…A study using an episodic FOK paradigm reported this brain region as contributing to memory awareness in cognitively diverse older adults including cognitively normal controls and patients with Alzheimer’s disease (Cosentino et al, 2015). One assumption to understand the alcohol-related impaired FOK - intact RCJs dissociation was that prospective FOK and retrospective RCJs both implicated online memory monitoring mechanisms but differed in that FOK judgments required additional self-inferential processes to generate accurate future estimations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with most types of dementia, including Alzheimer’s disease and Frontotemporal Dementia, have been shown to have impaired meta-cognition 6 . Impaired meta-cognition correlates with structural and functional brain abnormalities in parts of the frontal lobe important for monitoring task performance 24 and may particularly involve right frontal and right anterior insular regions 25 . Finally, loss of meta-cognition may relate to disrupted functional connectivity between these regions and regions involved in memory or other cognitive abilities 26 .…”
Section: Neuropsychology Of Decision-makingmentioning
confidence: 99%